Insights into the roles of long noncoding RNAs in the communication between plants and the environment - Yuan, Chao; He, Rui‐rui; Zhao, Wen‐long; Chen, Yue‐qin; Zhang, Yu‐chan (The plant genome, 2023)
In addition to coding proteins, RNA molecules, especially long noncoding RNAs (lncRNAs), have well‐established functions in regulating gene expression. The number of studies focused on the roles played by different types of lncRNAs in a variety of plant biological processes has markedly increased. These lncRNA roles involve plant vegetative and reproductive growth and responses to biotic and abiotic stresses. In this review, we examine the classification, mechanisms, and functions of lncRNAs and then emphasize the roles played by these lncRNAs in the communication between plants and the environment mainly with respect to the following environmental factors: temperature, light, water, salt stress, and nutrient deficiencies. We also discuss the consensus among researchers and the remaining challenges and underscore the exciting ways lncRNAs may affect the biology of plants. Core Ideas We summarize the classification, mechanisms, and functions of lncRNAs in plants. We emphasize the roles of lncRNAs in the communication between plants and the environment. We focus on the environmental factors including temperature, light, water, salt stress, and nutrient deficiencies.